2011
DOI: 10.1159/000324192
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Levels of Oxidative Stress Are Associated with Hospital Readmissions due to Acute Heart Failure

Abstract: Objectives: Inflammation and serum oxidative stress (OS) are important components in heart failure (HF) deterioration. In this study we tested the hypothesis that an increase in patients’ sera OS levels is associated with acute HF (AHF) readmissions. Methods: Thirty consecutive patients (mean age 71 ± 10 years) admitted with AHF were included in the study. Serum OS in these patients was measured in-hospital and repeatedly after discharge over a period of 8 weeks of follow-up in which we reordered patients’ HF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Researchers found that the serum of patients with liver cirrhosis had higher antioxidant activity than the non‐hepatitis B surface antigen (HBsAg) carriers, while the antioxidant activity of normal controls was significantly lower 28,29 . Tumor necrosis factor (TNF)‐α and transforming growth factor (TGF)‐β are significantly increased in patients with viral hepatitis, and oxidative damage is closely related to the pathological damage of hepatic fibrosis 30,31 . In HSC, phagocytosis of apoptotic bodies increases the production of intracellular oxygen free radicals which promotes the activation of HSC to increase liver fibrosis 32 .…”
Section: Oxidative Damagementioning
confidence: 99%
“…Researchers found that the serum of patients with liver cirrhosis had higher antioxidant activity than the non‐hepatitis B surface antigen (HBsAg) carriers, while the antioxidant activity of normal controls was significantly lower 28,29 . Tumor necrosis factor (TNF)‐α and transforming growth factor (TGF)‐β are significantly increased in patients with viral hepatitis, and oxidative damage is closely related to the pathological damage of hepatic fibrosis 30,31 . In HSC, phagocytosis of apoptotic bodies increases the production of intracellular oxygen free radicals which promotes the activation of HSC to increase liver fibrosis 32 .…”
Section: Oxidative Damagementioning
confidence: 99%
“…NO regulates changes in peripheral vascular tone, coronary blood flow and myocardial contractility, all important contributors in Heart failure (HF) disease. Moreover, inflammation and oxidative stress are also integral components in the progression of HF [3,4]. Accordingly, changes in eNOS activity and NO bioavailability may play an important role in the formation of reactive oxygen species and development of endothelial dysfunction, compromising cardiac performance and affecting HF progression [5].…”
Section: Introductionmentioning
confidence: 99%
“…The role of oxidative stress in the development of cardiovascular injuries has been reliably established. 2 Clinical and experimental studies have produced substantial evidence that oxidative stress, defined as an extreme production of reactive oxygen species relative to antioxidant defense, plays a role in HF. An increased concentration of reactive radicals, particularly superoxide, has been linked to peripheral endothelial dysfunction, peripheral hypoperfusion, and exaggerated sympathetic nerve activity in patients with HF.…”
Section: Introductionmentioning
confidence: 99%